TRADISI PATUNG KEPALA - ICHWAN NOOR (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2017)
In the history of culture , the artwork is the result of cultivation of the earliest discovered . In Europe in the 6000-10000 years ago are found paintings on the walls of the cave which is a handprint as impressive paintings . In Indonesia there is a cave Leang - Leang that still leaves traces of human artistic past , which is well-known in Europe was the discovery of a statue of Venus of Willendorf . This shows a desire to demonstrate to colleagues that